Case report: Early detection of mesenteric ischemia by intravital microscopy in a patient with septic shock - Praxenthaler, Janina; Kirchner, Carmen; Schwier, Elke; Altmann, Simon; Wittmer, Axel; Henzler, Dietrich; Köhler, Thomas (Frontiers in Medicine, 2022)
Gut ischemia is a frequent but underdiagnosed complication, especially in critically ill intensive care patients, and represents a special diagnostic challenge that can only be solved in an interdisciplinary manner. We report a case of a 54-year-old woman with acute mesenteric ischemia (AMI) as a cause of septic shock diagnosed by intravital microscopy (IVM) 2 days before visible necrotic changes in a multimodality approach. We show that intravital microscopy can be a serious alternative for the early diagnosis of mesenteric ischemia in the hands of the skilled. We use this case to discuss the value and clinical perspective of IVM in the intensive care setting.